Teachings of Abu Nasr Farabi on the Virtuous Civil Society in the Book "The City of Virtuous People (Fozil odamlar shahri)" (Eurasian Journal of Humanities and Social Sciences, 2023)
In the Eastern world, especially in our homeland Uzbekistan, living together as a community is a feeling that brings people closer to each other, supports each other and creates a basis for living, and has gained great importance in the development of society. Man, people, nation's thinking, spiritual views, lifestyle were formed and developed under the influence of society. When we talk about the high manifestations of our spirituality, such as kindness and generosity, characteristic of the people of the East and the people of our country, special attention should be paid to their socio-philosophical background.